Locus of Control Sebagai Moderator Komitmen Organisasi: Peran Persepsi Dukungan Organisasi dan Kepercayaan Terhadap Pemimpin - Kusumowardhani, Retno Pandan Arum; Ancok, Djamaludin (ANIMA Indonesian Psychological Journal, 2006)
This study examined the relationship of perceived organizational support and trust in leadership, to organizational commitment. This study also examined the moderating effect of locus of control on the relationship between those predictors and the criterion. Lecturers (N = 80) of a private university in Yogyakarta were surveyed using four related scales. The data were analyzed through regression analysis. Results show a) a significant relationship of perceived organizational support, trust in leadership, and locus of control to organizational commitment, b) perceived organizational support was positively related to organizational commitment, c) locus of control was negatively related to organizational commitment, and d) perceived organizational support was more strongly related to increased organizational commitment for external locus of control individuals than for internal locus of control individuals. Penelitian ini bertujuan menguji hubungan antara persepsi tentang dukungan organisasi dan kepercayaan terhadap pemimpin dengan komitmen organisasi. Penelitian ini juga bertujuan menguji efek moderasi dari locus of control dalam hubungan antara variabel-variabel tersebut. Subjek adalah dosen (N=80) sebuah perguruan tinggi swasta di Yogyakarta yang mengisi empat jenis skala. Hasil analisis regresi menunjukkan bahwa a) terdapat hubungan yang signifikan antara persepsi dukungan organisasi, kepercayaan terhadap pemimpin, dan locus of control dengan komitmen organisasi, b) persepsi tentang dukungan organisasi berhubungan positif dengan komitmen organisasi, c) locus of control berhubungan negatif dengan komitmen organisasi, dan d) persepsi tentang dukungan organisasi memiliki hubungan yang lebih kuat dengan komitmen organisasi pada individu dengan locus of control eksternal daripada individu dengan locus of control internal.